Changes in children’s and adolescents’ dietary intake after the implementation of Chile’s law of food labeling, advertising and sales in schools: A longitudinal study - Fretes, Gabriela; Corvalán, Camila; Reyes, Marcela; Taillie, Lindsey Smith; Economos, Christina D.; Wilson, Norbert L.W.; Cash, Sean B. (Springer, 2023)
Background In June 2016, a comprehensive food policy was implemented in Chile that included front-of-package warning labels on key nutrients of concern (total sugars, added saturated fats, sodium, and calories), child-directed food advertisement bans, and school regulations. The policy was implemented in 3 phases from 2016 to 2019 and the primary objective was to improve children’s food environments. This study’s objective was to assess changes in child and adolescent intake of key nutrients of concern (total sugars, saturated fats, and sodium) at school after the initial implementation of Chile’s Law of Food Labeling and Advertisement.